Epidemiology, risk factors, and genetics of endometrial cancer - Tempfer, Clemens; Steinke-Lange, Verena; Aretz, Stefan; Schmutzler, Rita; Ortmann, Olaf; Roemer, Thomas; Hanf, Volker; Widhalm, Simone; Reents, Nicola; Jud, Sebastian; Kommoss, Stefan; Nothacker, Monika; et al. (Die Gynäkologie, 2022)
Background Endometrial cancer (EC) is the fifth most common female malignancy and the most common pelvic malignancy. Effective strategies for early detection, prevention, and genetic assessment are discussed in this article. Aim To review the literature on epidemiology, risk factors, and genetics. Materials and Methods This article is based on the current recommendations of the German Society of Obstetrics and Gynecology for the diagnosis and treatment of women with EC. The current literature was summarized based on expert knowledge. Systematic searches in the Medline database and in Cochrane Reviews were performed. The quality of the evidence was rated according to the 2011 Oxford classification. Recommendations and statements were formulated by a representative group using structured consensus methods. Results In Germany, 2.7% of cancer-specific deaths are due to EC. The incidence of EC increases with age and the disease is most often diagnosed in the age group of 75- to 79-year-old women. The lifetime risk of EC is 1.9%. Risk-modulating factors of EC include long-term use of estrogens, progestogen therapy, oral contraceptives, high body mass index, and impaired glucose metabolism. In addition, physical activity and dietary aspects, such as the amount of fat and red meat consumed, as well as soja foods, dietary fibers, vitamins, and specific beverages such as tea and coffee, play an important etiological role. EC also has a genetic component. Immunohistochemical and/or molecular screening is warranted for all patients with EC and has a significant impact on the genetic counselling of affected families as well as on treatment decisions.
CRIS-Team WoS Importer:2022-07-29